Melkersson-Rosenthal Syndrome: Case Reports - Poyrazoğlu, Hatice Gamze; Canpolat, Mehmet; Gümüş, Hakan; Per, Hüseyin; Kumandaş, Sefer (Fırat University, 2011)
Melkersson Rosenthal Syndrome is a neuro-mucocutaneous granulomatous disease, characterized by recurrent facial nerve paralysis, orofacial edema and fissured tongue. The cause of Melkersson Rosenthall Syndrome is unknown, but genetic and acquired factors may play a role. This syndrome is very rare in childhood, it is more frequently seen in the second and the third decades of life. Classical triad of this syndrome is very rarely seen. MRS usually occurs as monosymptomatic or oligosymptomatic involment. The presence of two or one of the manifestations with granulomatous cheilitis in the biopsy is sufficient to make the diagnosis of Melkersson-Rosenthal Syndrome. Treatment is symptomatic and may include medical therapies such as nonsteroid anti-inflamatory drugs, steroids and antibiotics. Melkersson-Rosenthal Syndrome should be considered in differential diagnosis of recurrent facial paralysis. Here, we present two girls with classical triad of Melkersson Rosenthall Syndrome.

Melkersen Rozenthal sendromu tekrarlayan periferik fasiyal paralizi, orofasiyal ödem ve fissürlü dil triadı ile karakterize nöro-mukokütan granülomatöz bir hastalıktır. Nedeni tam bilinmemekle beraber genetik ve kazanılmış faktörler etiyolojide rol almaktadır. Çocukluk çağında nadir görülen bu sendrom hayatın 2. ve 3. dekadında daha sık görülür. Klasik triadın görülmesi nadirdir ve genellikle monosemptomatik veya oligo semtomatik tutulum izlenir. Bulgulardan bir veya ikisinin varlığında tanı için yüzdeki ödemden cilt biyopsisi yapılarak granülamotöz keilitin varlığının gösterilmesi gerekmektedir. Tedavi semptomatiktir ve medikal tedavi olarak steroid, non steroid anti-inflamatuar ilaçlar ve antibiyotikler kullanılabilir. Melkersson Rosenthal sendromu tekrarlayan fasiyal paralizilerin ayırıcı tanısında düşünülmesi gereken bir hastalıktır. Bu yazıda oldukça nadir görülmesi ve klasik triadın bir arada olması nedeniyle cilt biyopsisine gerek kalmadan Melkersen Rozenthal sendromu tanısı alan iki kız hasta sunulmuştur.
Melkersson-Rosenthal Sendromlu: İki Olgu